Oxford Handbooks Online 2014
DOI: 10.1093/oxfordhb/9780199686858.013.052
|View full text |Cite
|
Sign up to set email alerts
|

Simplicity in Perceptual Organization

Abstract: A long-standing debate in perception concerns the question of whether perceptual organization is guided by internal efficiency (the simplicity principle) or by external veridicality (the likelihood principle). This article focuses on the simplicity principle which is a modern information-theoretic version of Occam's razor, but also compares it to the likelihood principle which reflects classical information theory. Both principles can be modeled by Bayes' rule which combines quantifications of view-independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 93 publications
(79 reference statements)
2
11
0
Order By: Relevance
“…A similar advantage has been found with dynamic glass patterns5859, the regularities of which have been connected to symmetry60. Similarly, rapid consecutive presentation of different symmetrical patterns has been found to produce more accurate discriminations of orientations of axis of symmetry5455.…”
Section: Discussionsupporting
confidence: 66%
“…A similar advantage has been found with dynamic glass patterns5859, the regularities of which have been connected to symmetry60. Similarly, rapid consecutive presentation of different symmetrical patterns has been found to produce more accurate discriminations of orientations of axis of symmetry5455.…”
Section: Discussionsupporting
confidence: 66%
“…A dissociation between direct and indirect measures of perceptual organization has been reported by Schmidt and Schmidt (2013) , who demonstrated that grouping strength of different grouping rules (e.g., similarity by shape and similarity by brightness) did not correlate with priming effects of those rules. Hence, we propose that the objecthood effects reported here and shape similarity effects in previous studies of the Ebbinghaus illusion reflect an effect of figural “goodness” ( van der Helm, 2014 ; for a comprehensive review on Gestalt factors in visual perception see Peterson & Kimchi, 2013 ; Wagemans et al, 2012 ). Support to this hypothesis may be found in a study by Rose and Bressan (2002) , who showed that even when the target and flankers’ shapes were identical, the magnitude of the illusion varied for different shapes.…”
Section: Discussionsupporting
confidence: 49%
“…In this experiment, we collected ratings of stability (Liu et al., 2017; van der Helm, 2015) as well as of prototypicality (Rosch, 1975) for the Japanese calligraphies already used in our first experiment. Stability ratings were used to examine to what extent this dimension corresponds to the concept of perceptual balance for the calligraphies.…”
Section: Discussionmentioning
confidence: 99%
“…This habit is formed in individuals through their lifetime by living with gravitation, which forces them to arrange things in a stable way. In this respect, others also speak of “gravitational stability” (van der Helm, 2015). To examine whether visual balance actually means perceived stability for the Japanese calligraphies, we asked our participants to assess the stability of these stimuli.…”
Section: Methodsmentioning
confidence: 99%